Willingness to sacrifice for climate mitigation in representative samples of Indian adults - Dean Spears; Payal Hathi; Diane Coffey (Institute of Labor Economics (IZA), 2019)
Under the Paris Agreement, each country submits national pledges that reflect common but differentiated responsibility. Policy-makers therefore need to understand the mitigation policy interests of domestic populations, especially in developing countries where survey data are relatively scarce. Here we describe results from a new survey-experiment that is representative of adults in the Indian state of Rajasthan and city of Mumbai: most respondents report willingness to sacrifice to achieve climate mitigation.
Keywords: Q56; 330; environment; climate; India; electricity; survey; phone survey; development